Quality of life among leprosy patients in the western province, Sri Lanka - Liyanage, Nadeeja R.; Arnold, Mahendra; Wijesinghe, Millawage Supun D. (International Journal Of Community Medicine And Public Health, 2021)
Background: Leprosy can affect the quality of life (QOL) of a person in many ways. Deformities and disabilities in leprosy leads to physical impairment. The stigma associated with leprosy leads to social isolation, which affects patient psychologically. By assessing the QOL would give an in-depth understanding of the effects on leprosy in different dimensions of health. Methods: A descriptive cross-sectional study was conducted to assess the QOL of 572 adult leprosy patients attending clinics in the western province using a locally validated Sinhala version of the WHOQOL-BREF questionnaire. Consecutive sampling method was used and data were collected using an interviewer-administered questionnaire (IAQ). The scores ranged from 1 to 5 for overall QOL and overall general health questions. Results: The overall QOL had a mean score of 3.4 (SD=0.8) and overall general health had a mean of 3.6 (SD=2.2). The mean scores of domains of WHOQOL-BREF included physical 69.8 (SD=17.1), psychological 68.2 (SD=16.6), social 55.1 (SD=25.0), environment 64 (SD=18.3) in the sample. With regards to socio-demographic factors, a higher QOL was observed in patients <60 years, male sex, passed O/L or above and currently employed with an income of rupees forty thousand (200$) or more and living in a permanent house. Higher QOL was also observed in patients without disability and who perform daily activities alone. Conclusions: QOL of leprosy patients was higher in physical, psychological, environment domains and was lower in the social domain. Continuous awareness programmes should be conducted for health workers and community to early identification, which reduces disabilities and improve QOL.